Gates, Channels, and Switches: Elements of the Proteasome Machine. Issue 1 (January 2016) - Finley, Daniel; Chen, Xiang; Walters, Kylie J.
Abstract : The proteasome has emerged as an intricate machine that has dynamic mechanisms to regulate the timing of its activity, its selection of substrates, and its processivity. The 19-subunit regulatory particle (RP) recognizes ubiquitinated proteins, removes ubiquitin, and injects the target protein into the proteolytic chamber of the core particle (CP) via a narrow channel. Translocation into the CP requires substrate unfolding, which is achieved through mechanical force applied by a hexameric ATPase ring of the RP. Recent cryoelectron microscopy (cryoEM) studies have defined distinct conformational states of the RP, providing illustrative snapshots of what appear to be progressive steps of substrate engagement. Here, we bring together this new information with molecular analyses to describe the principles of proteasome activity and regulation. Trends: Docking of a substrate at the proteasome RP complex is mediated by ubiquitin recognition, but, to be degraded, the substrate must be translocated through a channel leading from the RP to the proteolytic CP complex. Given that the channel from the RP to the CP is narrow, translocation generally requires unfolding of the substrate. Hydrolysis of ATP supplies the mechanical force required for substrate unfolding and translocation. Protein loops that line the channel within the RP interact with substrate and move axially to direct vectorial motion of the substrate towards the CP. Ubiquitin promotes degradation, but, if not removed, can impede translocation because it resists unfolding. Ubiquitin is removed from the substrate either before substrate entry into the translocation channel or contemporaneously with this event, depending on the deubiquitinating enzyme. Rapid deubiquitination can preempt substrate degradation. Recent cryoEM studies indicate that the proteasome adopts distinct conformational states, which appear to be distinguishable as substrate-receiving or substrate-engaged states.